The joint dynamics of liquidity, returns, and volatility across small and large firms - Tarun Chordia; Asani Sarkar; Avanidhar Subrahmanyam (Federal Reserve Bank of New York, 2005)
This paper explores liquidity spillovers in market-capitalization-based portfolios of NYSE stocks. Return, volatility, and liquidity dynamics across the small- and large-cap sectors are modeled by way of a vector autoregression model, using data that spans more than 3,000 trading days. We find that volatility and liquidity innovations in one sector are informative in predicting liquidity shifts in the other. Impulse responses indicate the existence of persistent liquidity, return, and volatility spillovers across the small- and large-cap sectors. Lead and lag patterns across small- and large-cap stocks are stronger when spreads in the large-cap sector are wider. Consistent with the notion that private informational trading in large-cap stocks is transmitted to other stocks with a lag, order flows in the large-cap-stock decile predict both transaction-price-based and mid-quote returns of small-cap deciles when large-cap spreads are high.
Keywords: G10; G14; 330; market liquidity; market efficiency; short-horizon returns; Gesamtwirtschaftliche Liquidität; Aktienmarkt; Spillover-Effekt; VAR-Modell; USA; Markteffizienz